Cover Feature: A Photoredox Nozaki‐Hiyama Reaction Catalytic in Chromium (Eur. J. Org. Chem. 29/2022). Issue 29 (1st August 2022) - Calogero, Francesco; Potenti, Simone; Magagnano, Giandomenico; Mosca, Giampaolo; Gualandi, Andrea; Marchini, Marianna; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract : The Cover Feature celebrates Japanese chemists Prof. Hitosi Nozaki and Prof. Tamejiro Hiyama, who discovered the Cr‐mediated allyl addition to aldehydes. This work reports a catalytic photoredox version of the Nozaki‐Hiyama reaction, without any problem related to the use of stoichiometric Mn or Zn as reducing agents….Mondai arimasen! More information can be found in the Research Article by P. G. Cozzi et al .